The modern view on the problem of joint pathology rehabilitation - Nailya Sheveleva; Larissa Minbayeva (National Scientific Medical Center, 2016)
The article provides literature review that reflect a modern view on the problem of articular pathology treatment and rehabilitation. Step-by-step osteoarthritis management schemes, published in the leading recommendations (NICE, OARSI, HKOA) are presented. The results of modern clinical trials, systematic reviews and meta-analyzes on the use of various methods of physical therapy for joints diseases treatment from the standpoint of evidence-based medicine are analyzed. Etiopathogenetic and clinical substantiation for inclusion of physiotherapy measures in rehabilitation programs were given to help maximizing the impact on all links of the pathological process chain. The use of different methods and techniques of physical therapy for osteoarthritis is currently debated, because of the contradictory literature data. Low level of evidence does not allow including physical therapy in the leading guidelines of osteoarthritis management. The reasons for low level of evidence might be small samples and insufficient degree of randomization in the majority of studies. Different sensitivity of patients to physical therapy and presence of associated diseases necessitate individualization of rehabilitation program that makes further large-scale assessment of impact of the physical factors difficult. However, considering physical therapy infinite possibilities, scientists continue to actively explore, constantly improve and implement a lot of new, highly effective methods of physiotherapy in rehabilitation process of osteoarthritis, proving the prospects of this type of conservative therapy.